Selected features of Philippine English pronunciation among three groups of Ilocano speakers - Haloc, L. I; Dita, S. N (Journal of Modern Languages, 2024)
This paper describes the pronunciation of Philippine English by Ilocano speakers from three provinces of Region II in the Philippines: Nueva Vizcaya, Isabela, and Cagayan. All participants were born, raised, and educated in their respective provinces. The participants answered a questionnaire and were recorded reading a word list and structured dialog. The target pronunciation for analysis included the vowels /i/, /ɪ/, /ɛ/, and /e/, and the consonant pair /θ/ and /ð/, and two suprasegmental features: lexical stress and the intonation of question forms. To a certain extent, the findings were consistent with Llamzon's (1969) and Tayao’s (2004) findings on the features of Philippine English pronunciation. However, the findings suggest variation possibly due to the dialects of Ilocano that they speak. The study contributes to our understanding of the diversity in Philippine English pronunciation due to the multilingual nature of the country.